A comparative production and characterisation of fast pyrolysis bio-oil from Populus and Spruce woods. (1st January 2021) - Echresh Zadeh, Zahra; Abdulkhani, Ali; Saha, Basudeb
Abstract: This study focuses on the production and characterisation of fast pyrolysis bio-oil from hardwood ( Populus ) and softwood ( Spruce ) using a bench-scale pyrolysis reactor at two different temperatures. In this study, a mixed solvent extraction method with different polarities was developed to extract different components of bio-crude oil into three fractions. The obtained fractions were characterized by using gas chromatography and mass spectrometry (GC-MS). The effect of temperature on the production of bio-oil and on the chemical distribution in bio-oil was examined. The maximum bio-oil yield (71.20%) was obtained at 873 K for bio-oil produced from softwood ( Spruce ). In contrast, at a temperature of 773 K, the bio-oil yields were 62.50% and 65.40% for bio-oil obtained from hardwood ( Populus ) and softwood ( Spruce ) respectively. More phenolic compounds were extracted at a temperature of 773 K for bio-oil derived from softwood ( Spruce ) whereas the bio-oil obtained from hardwood ( Populus ) produced mostly furans, acids and sugar compounds at this temperature. For both types of bio-oil, a wide variety of chemical groups were identified at a temperature of 873 K in comparison to 773 K. Graphical abstract: Image 1 Highlights: The effect of temperature on the production of bio-oil from hardwood and softwood has been comprehensively discussed. The most efficient solvent extraction route for separating and analysing highly valued chemicals has been identified. Effect of temperature on chemical distribution in bio-oil has been investigated.